FEATURES OF FORMATION SCENARIOS OF THE FOOD INDUSTRY - Nozhenko , S.V. (The actual problems of regional economy development, 2016)
The article is devoted to the topic – the invention of approaches to enterprise development oil and fat industry. The goal – to identify features of formation scenarios for the food industry. The chosen methodology allowed to analyze and evaluate the functioning of state enterprises. Results are discovering the benefits of scenario planning to find ways of business development. Novelty – a rationale for the use of scenario planning for enterprise development oil and fat industry, developing a set of scenarios. The practical significance – providing specific scenarios for enterprises of oil and fat industry.